2021
DOI: 10.1080/1350293x.2021.1895264
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pedagogical intervention on early childhood professionals’ emotional availability to children with different temperament characteristics

Abstract: The purpose of this study was to evaluate the impact of pedagogical intervention on early childhood education professionals' emotional availability to children with different temperament characteristics. Participants were 136 children (intervention group = 87; control group = 49) aged 1-6 years from 16 early childhood and care centres in Finland. The PedaSens intervention was a 9-month programme that included theory and video-based training for the professionals. Adult-child interaction was assessed with the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…This study is truly an innovative use of the system, much like the earlier study by Soderberg et al, (2013) where they studied the therapy process using the EA System, and found that EA is associated with therapeutic alliance. Further, other studies have looked at teacher-child EA (Harkoma et al, 2021(Harkoma et al, , 2022Pinchover & Shulman, 2019), as well as professional childcare provider and child EA (described in Biringen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This study is truly an innovative use of the system, much like the earlier study by Soderberg et al, (2013) where they studied the therapy process using the EA System, and found that EA is associated with therapeutic alliance. Further, other studies have looked at teacher-child EA (Harkoma et al, 2021(Harkoma et al, , 2022Pinchover & Shulman, 2019), as well as professional childcare provider and child EA (described in Biringen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, does a specific intervention improve caregiver's interaction with children with a specific type of temperament in center‐based childcare? (see Harkoma et al, 2021 for an interesting approach). Relatedly, does an intervention have a positive impact on the wellbeing of all children, including, for example, relatively shy infants or children with higher levels of frustration?…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the significant contribution of caregiver–child interactions to the socio‐emotional development (Mortensen & Barnett, 2015; this study) highlights the importance of professional development aimed at strengthening the quality of caregiver–child interactions (Egert et al, 2020). Professional development should therefore aim at improving caregivers' skills to interact with children with different temperaments (Harkoma et al, 2021). In‐service professional development, coupled with knowledge of infants' temperament, may stimulate caregivers' positive interactions with various children in the group.…”
Section: Discussionmentioning
confidence: 99%
“…An attachment-and EA-based program to improve the teacher's EA, PedaSens, was conducted in Finland (Harkoma et al, 2021) and involves 3 months of training, including five 90-min sessions. Children were between the ages of 1 and 6 years This program can be characterized as attachment-as well as EA-based, in that the teachers are trained in how to be emotionally available to the children (with teams of teachers being trained through the use of video feedback as well as the transmission of information about how to interact with children).…”
Section: Prevention and Intervention Effortsmentioning
confidence: 99%